An initial examination of the effects of deviance regulation theory on normative perceptions. (2nd November 2018) - Dvorak, Robert D.; Kramer, Matthew P.; Stevenson, Brittany L.
ABSTRACT: Background: This study examines the effects of Deviance Regulation Theory (DRT) on changes in normative perceptions of protective behavioral strategies (PBS). Methods: Participants (n = 104 college student drinkers; 59.62% women) enrolled in a 6-week, web-based, longitudinal study to test the effects of a DRT intervention on indices of PBS use. Participants were assigned to either the high or low PBS norm group based on their self-reported PBS norms. Participants were randomized to receive either a positively framed message about individuals who do use PBS or a negatively framed message about individuals who do not use PBS. Participants reported the percent of their peers who they believed used PBS (PBS normative belief) each week for 6 weeks. Results: Participants who reported low preintervention PBS norms showed a moderate increase in mean PBS norms postintervention if they received a negatively framed message about those who do not use PBS. Participants who reported high preintervention PBS norms showed a slight, nonsignificant, increase in mean PBS norms postintervention if they received a positively framed message about those who do not use PBS. Conclusions: Both of these were counter to hypotheses and suggest DRT may anchor perceived norms, preventing an increase in normative beliefs